Sustainable Pangasius Aquaculture Management Strategy using Multidimensional Scaling (MDS) and Analytical Hierarchy Process (AHP) in Tulungagung Regency, East Java, Indonesia - Nurhabib, Asro; Sartimbul, Aida; Primyastanto, Mimit; Widodo, Maheno Sri; Handoko, Lugu Tri; Rahayu, Andra Rejekining; Martudi, Suharun (Faculty of Fisheries and Marine Universitas Airlangga, 2024)
Graphical Abstract Highlight Research The author mentioned four highlights from their research: Tulungagung Regency is East Java Province's major pangasius producer. MDS can assess sustainability across multiple dimensions. AHP enables the prioritization of strategies that must be implemented. The Pangasius aquaculture company in Tulungagung Regency is currently in a sustainable state. Abstract Aquaculture activities in Tulungagung Regency provide livelihoods for 12,050 households. Therefore, ensuring the sustainability of Pangasius aquaculture activities is crucial for the welfare of fish farmers. This study aims to analyze the sustainability of existing Pangasius aquaculture businesses in Tulungagung Regency, East Java, Indonesia, and to create a sustainable Pangasius aquaculture policy strategy. This quantitative study used Multi-Dimensional Scaling (MDS) and Analytical Hierarchy Process (AHP) analyses to determine the sustainability status of Pangasius aquaculture based on five dimensions: ecological, economic, social, institutional, and technological infrastructure. Among these dimensions, two are less sustainable, particularly infrastructure technology and the economy.